Reflexive approach in teaching students with visual impairment - selected theoretical issues - Kornelia Czerwińska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
In a model profile of a special education teacher described in pedeutological literature reflexive approach holds the leading position - beside skills and abilities based on theoretical and methodological knowledge.  The ability to be critical about one's own thinking and performance is particularly important in teaching of students who represent different mode of perception. Reflexive approach makes the teacher more open and sensitive to specific styles of learning about the material, natural, cultural and social reality by that group of students.  Such approach contributes to avoiding inappropriate pedagogical practices. The effectiveness of the teacher of the visually impaired (TVI) is not determined solely by the ability to apply theoretical knowledge in practice but also by the ability to reflect on the currently implemented and the completed activities. Reflexive approach of the teacher to their his/her own performance is as important in the phase of diagnosing special educational needs of the student with visual impairment as in the phase of planning, implementing and evaluating didactic activities. The TVI has to collect observations from various school situations and analyse dynamic interactions between the learning environment he designs and the current abilities and needs of a specific  student with visual impairment.  The TVI should be open to frequent changes  occurring in the analysed area.